Simply irresistible - Gellar, Sarah Gilliard 1977-; Flanery, Sean Patrick 1965-; Fiedler, John 1925-2005; Amiel, Jon 1948-; Caracciolo, Joe; Roberts, Judith 1934-; Tarlov, Mark (Twentieth Century Fox Home Entertainment, 1999)
Beautiful restaurant owner Amanda Shelton is falling head over heels for handsome, hard-driving executive Tom Bartlett. Unfortunately, Tom is too busy to recognize that she's truly the girl of his dreams...until Amanda put him under her tantalizing spell!